1995
DOI: 10.1055/s-0038-1649834
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Genetic Factors in Relation to Elevated Circulating Levels of Plasminogen Activator Inhibitor-1 in Caucasian Patients with Non-Insulin-Dependent Diabetes Mellitus

Abstract: SummaryTo investigate the interaction of metabolic and genetic factors in relation to PAI-1, genotype was determined at a 4G/5G polymorphism in the PAI-1 gene promoter and at a Hind III RFLP of the PAI-1 gene in 189 Caucasian NIDDM patients. PAI-1 levels were equivalent in each genotype group and PAI-1 activity correlated with fasting insulin (r = 0.45), triglyceride (r = 0.39) body mass index (r = 0.44), cholesterol (r = 0.17) and glucose (r = 0.15). The regression slope (B) of PAI-1 activity on triglycerides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
120
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(139 citation statements)
references
References 38 publications
16
120
3
Order By: Relevance
“…28 In addition, environmentally influenced factors such as triglycerides have been reported to interact with the PAI-1 4G/5G polymorphism to regulate plasma PAI-1 levels. 29,30 Furthermore, a relationship between smoking habits and degree of insulin resistance as well as higher PAI-1 activity has been found. 31 As illustrated (Table 1), the incidence of diabetes mellitus, arterial hypertension, mean levels of triglycerides, and the percentage of current smokers were not different between the two groups.…”
Section: Discussionmentioning
confidence: 93%
“…28 In addition, environmentally influenced factors such as triglycerides have been reported to interact with the PAI-1 4G/5G polymorphism to regulate plasma PAI-1 levels. 29,30 Furthermore, a relationship between smoking habits and degree of insulin resistance as well as higher PAI-1 activity has been found. 31 As illustrated (Table 1), the incidence of diabetes mellitus, arterial hypertension, mean levels of triglycerides, and the percentage of current smokers were not different between the two groups.…”
Section: Discussionmentioning
confidence: 93%
“…An association of the 4G allele with higher PAI-1 levels/antigen has been shown in patients with coronary artery disease, 2,3 patients with diabetes mellitus, 7 healthy subjects, 4 and postmenopausal women, 5 whereas only a weak relation was found in healthy women but not men, 42 and no association was found in patients 6 or first-degree relatives of patients with type 2 diabetes, 43 in healthy men, 44 or in families with premature and severe coronary heart disease. 45 Differences in the study populations with regard to factors affecting PAI-1 levels or the relation of the 4G/5G genotype and PAI-1, such as gender, 42 various underlying disease conditions (coronary artery disease, diabetes mellitus, and insulin resistance), 46 and concomitant medications, such as estrogen replacement therapy 5 or drugs that affect the reninangiotensin-aldosterone system, 5,46 may account for these differences to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that PAI-1 4G/5G genotype influences the relationship between serum triglycerides and PAI-1 antigen in diabetic patients, such that triglycerides and PAI-1 antigen correlate in individuals who are homozygous for the 4G allele but not in individuals who carry Ն1 copy of the 5G allele. 22 This genotype-specific effect of triglycerides has been attributed to the interaction of the PAI-1 4G/5G site and an adjacent VLDL triglyceridesensitive site in the promoter region of the PAI-1 gene. 45 In this study, we observed a similar genotype-specific effect of triglycerides on PAI-1 antigen in nondiabetic subjects with essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…21 Studies in patients with insulin resistance suggest that PAI-1 4G/5G genotype influences the relationship between triglycerides and PAI-1 expression. 22 Furthermore, there is a concentration-response relationship between glucose and plasma PAI-1 in 4G/4G homozygotes. 22 The present study tests the hypothesis that the PAI-1 4G/5G polymorphism also modulates the effect of activation of the RAAS on PAI-1 expression in patients with essential hypertension.…”
mentioning
confidence: 99%